O planejamento participativo da escola como prática inovadora - SANTOS, CLAUDINETE MARIA DOS; FERRI, LÚCIA MARIA CORREA GOMES; MACEDO, MARA ELISA CAPOVILLA MARTINS DE (Cadernos de Educação, 2012)
Para que a escola possa se organizar de formaeficiente e eficaz e cumprir suas funções sociais, oplanejamento participativo evidencia-se como recursodialógico e instrumento de organização do trabalho escolarpara as inovações pretendidas, compreendida comoorganização autônoma de trabalho conjunto e instânciaexecutiva das políticas públicas. Dessa concepção deriva aelaboração do projeto pedagógico, alinhado aos pressupostosda gestão participativa como instrumento que contribui para amelhoria da qualidade do ensino e superação da centralizaçãodas decisões, improvisos e ações isoladas.Palavras-Chave: planejamento; participação; qualidade deensinoAbstract: For the school to be efficiently organized andeffectively in fulfilling their social tasks, the participatoryplanning becomes evident as dialogical resource andinstrument of anticipation and organization of school work forthe innovations intended, where the school turns to beunderstood as autonomous organization of joint work andexecutive body of public policy. This school concept leads tothe preparation of the pedagogical project, supported on thedemocratic principles, aligned with the assumptions of theparticipatory management as a toll that contributes for theimprovement of the quality of education and overcoming ofthe centralization of decision-making, improvisation andisolated actions.Keywords: planning; participation; quality of education